Pathophysiological analysis of systemic and renal disregulation of pathological processes in the damage of proximal tubule in the nephrolithiasis - Rohovyi, Yurii; Oleksandr, Ariychuk (Journal of Education, Health and Sport, 2019)
The pathogenesis of urolithiasis in the modern view lies disregulating the pathological process of primary surplus mobilization reactions of protection, which leads to their further transformation in the reaction of damage that is the underlying basis for the formation of vicious circles. 299 patients with nephrolithiasis were examined, 10 patients were in the control group. Found that systemic and renal dysregulation pathological processes of stone the size of stones of 0.6 – 1.0 cm, top, middle cup the upper third of the ureter led to the formation of large and small “vicious circles”. Renal and extrarenal dysregulation pathological processes contributed to the increase in damage to the proximal tubule, since the primary damage to the said nephron. Department is not able to mobilize protective adaptive reactions aimed at increasing the excretion of acids and protein reabsorption, since they require additional energy costs. The use of the drug blemaren in nephrolithiasis reveals protective properties to reduce the manifestations of systemic and renal dysregulation pathological processes and promotes the rupture of formed large and small “vicious circles" with a decrease in proteinuria, the level of tumor necrosis factor-α, improving the transport of sodium ions, fibrinolytic activity of urine and it is advisable to develop guidelines for further use in the clinic of the drug blemaren as a promising method of treatment of urolithiasis.